2017
DOI: 10.1039/c6ra27401c
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a low electrical percolation threshold and superior mechanical performance in poly(l-lactide)/thermoplastic polyurethane/carbon nanotubes composites via tailoring phase morphology with the aid of stereocomplex crystallites

Abstract: We demonstrate a facile strategy to fabricate highly conductive PLLA/TPU/CNTs composites with very low percolation threshold and good stiffness–toughness balance via constructing stereocomplex crystallites in PLLA melt to tailor phase morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…21 CNTs are also used to modify the properties of polymer-polymer composites. [22][23][24] For example, when the content of MWCNTs was 5 wt% in PET/LDPE blends (mass ratio ¼ 20 : 80), Cardinaud et al 22 found that the MWCNTs had little effect on the rheological properties of the blends. The melt viscosity increased as the content of the MWCNTs increased.…”
Section: Introductionmentioning
confidence: 99%
“…21 CNTs are also used to modify the properties of polymer-polymer composites. [22][23][24] For example, when the content of MWCNTs was 5 wt% in PET/LDPE blends (mass ratio ¼ 20 : 80), Cardinaud et al 22 found that the MWCNTs had little effect on the rheological properties of the blends. The melt viscosity increased as the content of the MWCNTs increased.…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 gives the values for φc with the PLA percentage of the blend. Depending on the conditions for the selective localization of CB at the interface or in one of the polymer phases, in this case PHBV, φc changes with the relative amounts of the polymer phases in the system [59,60]. Other researchers have seen a similar optimization in the mechanical properties for a related 80:20 system [61].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a variety of methods have been proposed to lower the percolation threshold of the conductive composites 7–9 . Among them, a constructive way is to construct conductive composites with double percolation structure 10–12 .…”
Section: Introductionmentioning
confidence: 99%